2004
DOI: 10.1103/physrevlett.92.072301
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanism ofH0Dibaryon Production in Proton-Proton Interactions from Parton-Based Gribov-Regge Theory

Abstract: A novel mechanism of H 0 and strangelet production in hadronic interactions within the Gribov-Regge approach is presented. In contrast to traditional distillation approaches, here the production of multiple (strange) quark bags does not require large baryon densities or a QGP. The production cross section increases with center of mass energy. Rapidity and transverse momentum distributions of the H 0 are predicted for pp collisions at E lab = 160 AGeV and √ s = 200 GeV. The predicted total H 0 multiplicities ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…to arrive on Earth or other place of the Galaxy. These results appeared to be in accordance with terrestrial experiments at RHIC which have not confirmed the existence of the SQM nor proved that it does not exists [60][61][62].…”
Section: Final Remarkssupporting
confidence: 65%
“…to arrive on Earth or other place of the Galaxy. These results appeared to be in accordance with terrestrial experiments at RHIC which have not confirmed the existence of the SQM nor proved that it does not exists [60][61][62].…”
Section: Final Remarkssupporting
confidence: 65%
“…Generally speaking, our results appear to be consistent with the fact that absolutely stable SQM has not been observed up to the present. The experiment with STAR at RHIC has not confirmed the existence of SQM nor proved that it does not exist [48][49][50]. The low values of G 2 with respect to the ones in [36,37] would provide a possible explanation for the absence of absolutely stable SQM signature.…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%
“…It is therefore treated the same way as all the other hadrons. A similar approach was recently introduced to study H 0 production in pp interactions [26].…”
mentioning
confidence: 99%